Interactive augmented reality for preschool science education - Muhamamad Iman, Mohd Salleh (2014)
This project is about a mobile learning application using Augmented Reality as the medium. This apps is made for preschool student age 4-6. This project will use a physical book and android apps to interact with the AR technology. This book consist of 4 chapter that's is Anggota Badan, Haiwan, Kenderaan and Planet. This project can be used as a learning tool to replace the traditional method of teaching. A marker will be placed in the book as a platform for the apps to interact. User need to load the apps and place the camera view on the marker to interact with the AR technology.